Compound refractive lenses as prefocusing optics for X‐ray FEL radiation. (19th February 2016) - Heimann, Philip; MacDonald, Michael; Nagler, Bob; Lee, Hae Ja; Galtier, Eric; Arnold, Brice; Xing, Zhou
Abstract : A prefocusing compound refractive lens was implemented for the Matter under Extreme Conditions Instrument at the Linac Coherent Light Source. A significant improvement in the beamline transmission was calculated and observed at 5 keV. Abstract : The performance of X‐ray free‐electron laser beamlines may be limited by the angular aperture. Compound refractive lenses (CRLs) can be employed to prefocus the X‐ray beam, thereby increasing the beamline transmission. A prefocusing CRL was implemented in the X‐ray transport of the Matter under Extreme Conditions Instrument at the Linac Coherent Light Source. A significant improvement in the beamline transmission was calculated over the 3–10 keV photon energy range. At 5 keV, the relative X‐ray intensity was measured and a factor of four increase was seen in the beamline transmission. The X‐ray focus was also determined by the ablation imprint method.